ANALISIS KEMAMPUAN PENALARAN MATEMATIS SISWA DALAM MENYELESAIKAN SOAL SETARA PISA KONTEN GEOMETRI - Orin Asdarina; Masriyah Ridha (Program Studi Pendidikan Matematika, Universitas Bina Bangsa Getsempena, 2020)
The purpose of this study was to determine students’ mathematical reasoning abilities in solving PISA equivalent geometry content problems at the class VIII of SMP Negeri Unggul Tunas Nusa and these factors can influence students’ mathematical reasoning abilities in solving equivalent questions of PISA geometry content grade VIII of SMP Negeri Unggul Tunas Nusa. The research design used in this study was descriptive research. The subjects in this study were 30 students from grade VIII- SMP Negeri Unggul Tunas Nusa. Data collection was obtained through the distributing of tests and interviews. From the results of the data analysis, it was concluded that the mathematical reasoning students’ ability in Solving on geometry content problems in grade VIII of SMP Negeri Unggul Tunas Nusa was in the very low category. The ability of students’ on mathematical reasoning at the indicator I was 21.56%, indicator II was 33.49%, indicator III was 16.11%, and indicator IV was 15.56%. The cause of the obstacles faced by students in solving geometry content material problems is that students were not accustomed to solving non-routine questions, a little bit complicated, and require a high level of problem solving as the questions given to students were equivalent to PISA problems, the ability of students to mastery of the material is limited and cannot suitable to the concepts that have been studied with the problem being worked on. Abstrak Tujuan dari penelitian ini adalah untuk mengetahui kemampuan penalaran matematis siswa dalam menyelesaikan soal setara PISA konten geometri di kelas VIII SMP Negeri Unggul Tunas Nusa dan faktor-faktor yang mempengaruhi kemampuan penalaran matematis siswa dalam menyelesaikan soal setara PISA konten geometri kelas VIII SMP Negeri Unggul Tunas Nusa. Rancangan penelitian yang digunakan dalam penelitian ini merupakan penelitian deskriptif. Subjek dalam penelitian ini adalah 30 siswa dari kelas VIII-Nusa SMP Negeri Unggul Tunas Nusa. Pengumpulan data diperoleh melalui pemberian tes dan wawancara. Dari hasil analisis data, diperoleh kesimpulan bahwa kemampuan penalaran matematis siswa dalam mengerjakan soal konten geometri kelas VIII Nusa SMP Negeri Unggul Tunas Nusa berada dalam kategori sangat rendah. Kemampuan penalaran matematis siswa pada indikator I sebesar 21,56%, pada indikator II sebesar 33,49%, pada indikator III sebesar 16,11%, dan indikator IV sebesar 15,56%. Penyebab dari kendala yang dihadapi siswa dalam menyelesaikan soal materi konten geometri adalah siswa tidak terbiasa menyelesaikan soal-soal nonrutin, sedikit rumit, serta memerlukan tingkat pemecahan masalah yang tinggi seperti soal yang diberikan kepada siswa adalah soal setara PISA, kemampuan siswa dalam menguasai materi yang terbatas dan siswa tidak mampu mengaitkan konsep yang telah lama dipelajari dengan soal yang sedang dikerjakan. Kata Kunci : Kemampuan Penalaran Matematis, PISA